PERAN STRATEGI PEMASARAN UMKM MELALUI DIGITAL MARKETING SEBAGAI UPAYA MENINGKATKAN DAYA SAING PRODUK BERBASIS KEARIFAN LOKAL DI PULAU ADONARA KABUPATEN FLORES TIMUR - Kurniawati, Merlyn; Fadhilah, Lia Nur; Nastiti, Dyah Wahyu (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the economy of every country. Local wisdom is an element of the cultural traditions of a nation's people. MSME Marketing Strategy to increase product competitiveness is a step for MSMEs to survive in the business world. Preservation of Local Wisdom is expected to be able to make an increase in competitiveness in increasing marketing and supported by the existence of Digital Marketing technology in marketing products is expected to be able to increase the competitiveness of local wisdom identity products. The purpose of this study is that there has been no scientific study specifically in East Nusa Tenggara on the Marketing Strategy of MSMEs with basic local wisdom, namely weaving craftsmen to follow the development of digitalisation. The research was conducted by conducting interviews with 80 weaving craftsmen by designing marketing strategy tools using SWOT analysis. The competitiveness of weaving products can be increased through digital marketing strategies and creating unique weaving motifs that reflect tradition and culture and adjust to current trends. In addition, they must regularly attend digital marketing training so that the products produced can be sold directly on digital platforms and optimise product competitiveness opportunities by following market trends so that they can compete not only in the local market but begin to penetrate into national and foreign markets. Keywords: Digital Marketing Strategy; Product Competitiveness; Local Wisdom